RANCANG BANGUN SISTEM INFORMASI INVENTORY BARANG PADA TOKO HUSEIN BERBASIS WEB DENGAN METODE MIN-MAX - Pembuain, Fince; Daetalova, Sarah Insani; Haliza, Syifa Nur; Bani, Alexius Ulan; Ramos, Samuel (Journal of Information System, Informatics and Computing, 2025)
Inventory is a crucial factor in retail operations. Currently, the inventory information system at Toko Husein is still conducted manually using logbooks, leading to stock inaccuracies, data loss risks, and reporting delays. This study aims to design a web-based inventory information system using the Min-Max method to determine minimum, maximum, and safety stock levels to ensure product availability. The research methods included observation, interviews, and literature review, with system development using PHP programming language and MySQL database. System design was modeled using Unified Modeling Language (UML). The result of this research is a system capable of recording incoming and outgoing goods transactions, presenting real-time inventory reports, and providing reorder point notifications based on Min-Max calculations. Black Box testing indicates that the system functions validly. This system is expected to improve stock management efficiency and data accuracy at Toko Husein.